MANAGING VALUE-ADDED TAX ISSUES IN VILLAGE BUDGET EXECUTION - Fitradina Antares; Nurhidayati Nurhidayati (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
In administering the Village Budget, one of the village treasurer's obligations is compliance with the tax obligations, including value-added tax (VAT). The concept of VAT collection by the village treasurer differs from the general mechanism where sellers of goods or services confirmed as taxable entrepreneurs are VAT collectors. The village treasurer's mechanism for collecting VAT is unique; the village treasurer requests a bill that includes the amount of VAT owed from the partner taxable entrepreneurs. Village treasurer compliance in carrying out tax obligations still needs to improve. From previous research, the factors influencing village treasurer tax compliance are low awareness and level of tax knowledge and the assumption that taxes are complicated. By using the qualitative descriptive approach, this study aims to explain how to manage finances, especially in collecting VAT, depositing VAT payable that has been collected, and reporting VAT. This study reveals that VAT administration is more straightforward than some village treasurers assume.